ChemInform Abstract: Predicting Gold‐Mediated Catalytic Oxidative‐Coupling Reactions from Single Crystal Studies. Issue 21 (27th May 2014) - Xu, Bingjun; Madix, Robert J.; Friend, Cynthia M.
Abstract Review: 32 refs.